Theses and Dissertations Completed in Family and Consumer Sciences: 2017. (1st December 2018) - Wilmarth, Melissa J.; Ingram, Suzannah
Abstract : The annual survey of graduate programs in family and consumer sciences at U.S. universities and colleges was completed between June and August 2018. The goal was to compile a list of theses and dissertations completed in 2017 from all areas of family and consumer sciences. Requests for information on graduation, titles, and authors were sent by e‐mail to institutions with family and consumer sciences programs. A total of 286 theses and 200 dissertations were reported from 32 universities and colleges. The following is a report of the complete information provided by institution respondents by subject category including author, title of thesis or dissertation, degree‐granting institution, and name of student's advisor.